Assessing the Effects of Product Quality and Environmental Management Accounting on the Competitive Advantage of Firms - Alan S. Dunk (Australasian Accounting, Business and Finance Journal, 2007)
Arguments have been made in the literature that product quality provides a basis for establishing and maintaining a firm’s competitive advantage. Proposals suggest that the framework provided by environmental management accounting facilitates product quality having the attributes that are likely to contribute to competitive advantage, and hence it is likely that environmental accounting plays an influential role in that relation. The purpose of this study is to examine empirically whether there is evidence for environmental management accounting impacting on the relation between product quality and competitive advantage. These findings support the view that environmental management accounting has an important role to play in firms. Specifically, the results of the study suggest that product quality contributes to a firm’s competitive advantage when the reliance on environmental management accounting is high. However, it fails to do so when the reliance on environmental management accounting is low.
Keywords: environmental management accounting; product quality; competitive advantage